Israel in a New Middle East: How to Respond? - Bryc, Agnieszka (The Copernicus Journal of Political Studies, 2018)
Israeli foreign policy, its mechanisms, conditions, as well as driving forces is a complex phenomenon composed of intersecting elements of security, defense, and foreign interests that are inseparably braided. Generally speaking, there are at least four main interests which determine states’ foreign activity, firstly security of the state and its territory, secondly economy and development, thirdly international position, prestige among other states, and lastly international society common benefits. The only way to understand Israel’s international conduct is to look deeper into its national identity, political tradition, and historical burden as well. So the goal of this paper is to study the priorities of the Israeli foreign policy, particularly while the so called Arab Spring, crisis over Iranian nuclear program, and the changes in the Middle East. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14763